2020
DOI: 10.1007/s12020-020-02256-x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of high-carbohydrate and high-monosodium glutamate diet related to the increase of likelihood of type 2 diabetes mellitus: a review

Abstract: Diabetes is one of the most common metabolic diseases. Aside from the genetic factor, previous studies stated that other factors such as environment, lifestyle, and paternal-maternal condition play critical roles in diabetes through DNA methylation in specific areas of the genome. One of diabetic cases is caused by insulin resistance and changing the homeostasis of blood glucose control so glucose concentration stood beyond normal rate (hyperglycemia). High fat diet has been frequently studied and linked to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 118 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…
Fig. 1 Scheme showing mechanism for induction of obesity from consumption of diets high in MSG via activating increased expression of PPAR-Y and Alpha [ 43 ].
…”
Section: Monosodium Glutamate and Metabolic Disordersmentioning
confidence: 99%
“…
Fig. 1 Scheme showing mechanism for induction of obesity from consumption of diets high in MSG via activating increased expression of PPAR-Y and Alpha [ 43 ].
…”
Section: Monosodium Glutamate and Metabolic Disordersmentioning
confidence: 99%
“…Monosodium glutamate (MSG) consumption has risen dramatically over three decades [5]. People in Asia often eat foods that contain high carbohydrates [6,7] with the addition of MSG as a flavor enhancer [8][9][10][11][12][13][14]. MSG consumption in Southeast Asia is 2-3 times more than people in Europe [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous literature study (Nathanael et al, 2020) showed that several gene expressions changed when animal models, cell culture, or epidemiological study applied a diet with a high carbohydrate or MSG. However, such study is a comprehensive study in which no central genes which may become determining factor(s) in the formation of T2D are concluded.…”
Section: Introductionmentioning
confidence: 99%